Potential and limitations of regulatory T-cell therapy in solid organ transplantation. (September 2014) - Govender, Lerisa; Pascual, Manuel; Golshayan, Dela
<x xml:space="preserve">Abstract</x> Over the past few years, the therapeutic potential of Treg has been highlighted in the field of autoimmune diseases and after allogeneic transplantation. The first hurdle for the therapeutic use of Treg is their insufficient numbers in non-manipulated individuals, in particular when facing strong immune activation and expanding effector cells, such as in response to an allograft. Here we review current approaches being explored for Treg expansion in the perspective of clinical therapeutic protocols. We describe different Treg subsets that could be suitable for clinical application, as well as discuss factors such as the required dose of Treg, their antigen-specificity and in vivo stability, that have to be considered for optimal Treg-based immunotherapy in transplantation. Since Treg may not be sufficient as stand-alone therapy for solid organ transplantation in humans, we draw attention to possible hurdles and combination therapy with immunomodulatory drugs that could possibly improve the in vivo efficacy of Treg.